Catalyst Development for the Synthesis of Ozonides and Tetraoxanes Under Heterogeneous Conditions: Disclosure of an Unprecedented Class of Fungicides for Agricultural Application. Issue 21 (19th February 2020) - Yaremenko, Ivan A.; Radulov, Peter S.; Belyakova, Yulia Y.; Demina, Arina A.; Fomenkov, Dmitriy I.; Barsukov, Denis V.; Subbotina, Irina R.; Fleury, Fabrice; Terent'ev, Alexander O.
Abstract: The catalyst H3+ x PMo12− x +6 Mo x +5 O40 supported on SiO2 was developed for peroxidation of 1, 3‐ and 1, 5‐diketones with hydrogen peroxide with the formation of bridged 1, 2, 4, 5‐tetraoxanes and bridged 1, 2, 4‐trioxolanes (ozonides) with high yield based on isolated products (up to 86 and 90 %, respectively) under heterogeneous conditions. Synthesis of peroxides under heterogeneous conditions is a rare process and represents a challenge for this field of chemistry, because peroxides tend to decompose on the surface of a catalyst . A new class of antifungal agents for crop protection, that is, cyclic peroxides: bridged 1, 2, 4, 5‐tetraoxanes and bridged ozonides, was discovered. Some ozonides and tetraoxanes exhibit a very high antifungal activity and are superior to commercial fungicides, such as Triadimefon and Kresoxim‐methyl. It is important to note that none of the fungicides used in agricultural chemistry contains a peroxide fragment. Abstract : Being better : A heterogeneous catalyst was developed for the peroxidation of 1, 3‐ and 1, 5‐diketones with hydrogen peroxide with the formation of bridged 1, 2, 4, 5‐tetraoxanes and bridged 1, 2, 4‐trioxolanes with yield up to 86 and 90 %, respectively. A new class of antifungal agents for crop protection, that is, cyclic peroxides, was discovered. Some ozonides and tetraoxanes exhibit a very high antifungal activity and are superior to commercial fungicides.